Barriers to Success: Exploring the Challenges of 7th Semester English Education Students in PPL Program - Surayawati, Sri Suci; Ervina, Ema; Rohmatillah (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This research investigates the challenges encountered by seventh- semester English Education students at Raden Intan Lampung State Islamic University during their Field Experience Practice (PPL), a mandatory course designed to enhance their teaching knowledge and skills. Employing a descriptive qualitative approach, interviews were conducted with 25 students to gather data. The findings revealed a range of challenges categorized as follows: procedural category faced by 2 students, managerial category experienced by 11 students, psychological category encountered by 2 students, instructional challenges affecting 8 students, and professional category for 2 students. Notably, the primary challenges identified were related to classroom and time management. The research recommends expanding the perspectives of supervising teachers, students, and the broader school environment to gain deeper insights into the challenges and potential solutions associated with the PPL program